MORPHOLOGICAL AND METABOLIC DISORDERS IN THE MANDIBLE AND INCISOR OF RATS UNDER THE INFLUENCE OF SALTS OF HEAVY METALS AND THEIR CORRECTION OSSEIN-HYDROXYAPATITE COMPLEX - Романюк, А.М.; Коробчанська, А.Б.; Сауляк, С.В.; Романюк, С.А. (World of Medicine and Biology, 2015)
In the experiment on 68 adult rats was to show the features of violation of the morphological structure and chemical composition of mandibular’s bone and incisors of rats under the action on the body salts of chromium, lead, zinc, iron, copper, manganese, and explore the possibility of using ossein-hydroxyapatite complex for correction of changes. It has been shown that readaptation period after the use of heavy metals on the background of correcting therapy the features more favorable, but the full normalization of the studied parameters does not occur even after 60 days. Keywords: morphology, mineral composition, the mandible, incisor, bone, heavy metal salts, ossein-hydroxyapatite complex. It was found that excess intake of heavy metals into the body is followed by their accumulation in hard tooth structures. It is known that cations and anions of heavy metals salts (HMs) can affect the hard tissues of the tooth in different ways causing the enamel strength inhibition. Increased level of lead, magnesium and manganese in enamel reduces the caries resistance. The imbalance of certain elements Al, F, P, Zn, Fe, Si, Mg, Cu is followed by the development of pathological abrasion of hard tooth tissue . At the same time the morphogenetic mechanisms of these disorders in bone tissue of the lower jaw are not studied enough. The objective: to study the peculiarities of morphological and metabolic disorders in the mandible and incisor of rats under influence of salts of heavy metals and their correction ossein-hydroxyapatite complex. The research was carried out on 68 white mature rats - males, divided into two groups: control and experimental. During 1 month the testing animals of the second group had been taking water with the excessive amount of HMs: zinc – 5 mg / l, copper – 1 mg / l, iron – 10 mg / l, manganese – 0.1 mg / l, lead – 0.1 mg / l and chromium – 0.1 mg / l. The material was examined in 1, 15, 30 and 60 days after discontinuance of taking the HMs. The cuts were stained with hematoxylin - eosin and Van Gieson’s picro - fuchsin. Digital data were processed by computer program AtteStat 12.0.5. Quantitative chemical analysis of lower jaw and incisors was carried out with the help of atomic absorption spectrophotometer C-115M1. By drying in drying chamber at 105º C to constant weight the moisture content was determined. The dried tissue was burning in porcelain crucibles in a muffle furnace at 450 º C for 48 hours. The total amount of organic and mineral substances in the solid residue was determined. The received ash was dissolved in 10% hydrochloric and nitric acids. According to the standard procedure the amount of zinc (wavelength - 213.9 nm), copper (wavelength - 324.7 nm), lead (wavelength - 283.3 nm), manganese (wavelength - 279.5 nm), chromium (wavelength - 357.9 nm), and iron (wavelength - 248.3 nm) was determined. Digital data were processed by computer program AtteStat 12.0.5. The experiments on testing animals were carried out in accordance with the regulations adopted by the European Convention for the Protection of Vertebrate Animals used for Experimental and other Scientific Purposes (Strasbourg, 1986), "General ethic rules about experiments on animals" approved by the I National Congress of Bioethics (Kyiv, 2001) and the Law of Ukraine "On protection of animals from cruelty» № 3477-IV from 21.02.2006. Under the influence of combination of heavy metals salts in bone tissue of lower jaw the features of significant slowing of the intensity of bone formation processes in compact and cancellous substances was found. Deceleration of appositional growth and disorders of bone matrix ossification, emersion of significant hypomineralization areas in ground substance and its swelling were observed. Proliferative activity of bone cells slowed, resorption changes in bone tissue intensified. Compact size of bone tissue of the lower jaw was disordered and did not recover during readaptation period even after 60 days of observation, as far as in bone tissue the dystrophic and osteoporotic changes were developed. In condylar cartilage the features of slowing of growth processes were also observed as well as intensification of resorption of cansellous bone tissue and unevenness of mineralization of ground substance. Subchondral osteogeny area narrowed to 9,78% (p